Ultrafast CSpiro-O dissociation via a conical intersection drives spiropyran to merocyanine photoswitching - Prager, Stefan; Burghardt, Irene; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2014)
The mechanism of the photochemical conversion of spiropyran to merocyanine is investigated theoretically. Calculations were performed at TD-DFT/ωB97XD/cc-pVDZ level of theory, which shows good agreement with the reference RI-CC2 method. A two-dimensional scan of the potential energy surface has been performed along the C-O distance and the central torsion angle in the ground state and in the first excited state, where the reaction takes place. Starting at the Franck-Condon geometry, the energy of the first excited state decreases in the direction of the C-O dissociation while the ground-state energy increases. This leads to a barrierless C-O bond dissociation in the first excited state. While relaxing on the S1 PES toward longer C-O distances, the torsion angle hardly changes, but other coordinates start to vary, leading to a conical intersection of the ground state and the first excited state at a C-O distance of about 3.4 Å. Passing the conical intersection, the reaction continues on the ground-state PES. At these large C-O distances, either barrierless Cspiro-O rebinding occurs that quenches spiropyran isomerization or rotation around the central torsion angle occurs that leads to merocyanine. For the latter an energy barrier of 0.1 eV must be overcome explaining the low quantum yield of spiropyran to merocyanine photoswitching.